Electrochemical behaviour of proteins at graphite electrodes. II. Electrooxidation of amino acids - Brabec, V; Mornstein, V (Biophysical chemistry, 1980)
Electrochemical oxidation of L,alpha-amino acids at a paraffin-wax impregnated spectroscopic graphite electrode (WISGE) was studied by means of linear sweep, cyclic, phase-sensitive alternating current and differential pulse voltammetric techniques. It was found that out of the amino acids usually occurring in proteins only tyrosine, tryptophan, histidine, cystine, cysteine and methionine were oxidized at the WISGE. At relatively low concentrations of amino acids (up to ca. 2 x 10(-4) M) the electrode process in which the amino acids are oxidized at the WISGE has the characteristics of an irreversible reaction controlled by diffusion. Coulometric measurements showed that oxidation of tyrosine and tryptophan at the WISGE, i.e. of amino acids which are responsible for the oxidizability of proteins at graphite electrodes, is a two-electron process. At higher concentrations of tyrosine-and tryptophan (above ca. 2 x 10(-4) M) adsorption of the oxidation product of these amino adds was demonstrated.